Integrating E-business models for government solutions : citizen-centric service oriented methodologies and processes - Chhabra, Susheel; Muneesh Kumar (Hershey PA : Information Science Reference, 2009)
'The objective of this book is to examine issues and promote research initiatives in the area of effectiveness in e-government by suggesting integrated e-business models for government solutions, through citizen-centric service oriented methodologies and processes'--Provided by publisher.
Includes bibliographical references (p. 279-303) and index.
Keywords: Internet in public administration; Administrative agencies -- Customer services; Administrative agencies -- Management; Executive departments -- Customer services; Executive departments -- Management; Consumer satisfaction